SUSTAINABILITY ANALYSIS OF LIGHTWEIGHT CONCRETE TECHNOLOGIES: OPTIMIZING CLC PANEL THICKNESS FOR STRUCTURAL PERFORMANCE AND ENVIRONMENTAL FOOTPRINT REDUCTION: English - Budi, Gatot Setya; Sutandar, Erwin; Prasetijo, Joewono; Parabi, Ashraf Dhowian (Journal of Applied Engineering Science, 2025)
This research examines the optimization of Cellular Lightweight Concrete (CLC) panel thickness to balance structural performance with environmental sustainability for construction on soft, peaty terrain in West Kalimantan, Indonesia. Laboratory testing was conducted on precast CLC slab panels (1,600 mm × 600 mm) with thicknesses varying from 70 mm to 130 mm. The panels were fabricated using a mixture of foam agent, cement, water, and sand, resulting in specimens with an average density of 1,287.26 kg/m³, while achieving a compressive strength of 3.42 MPa. The unidirectional slabs with double M5 (wiremesh) reinforcement were tested after a 28-day curing period. Results showed that thicker panels exhibited superior bending load capacity, with L/240 design flexural capacity ranging from 1.61 kN to 6 kN for thicknesses between 70 mm to 130 mm. Analysis determined that panels exceeding 100 mm thickness successfully sustained the design load of 250 kg (25 kN) minimum load for flexural capacity, making them suitable for 1,600 mm spans. The study establishes a minimuml thickness threshold that balances minimal material usage with adequate structural performance, offering an environmentally responsible building solution that reduces material consumption, transportation energy requirements, and foundation loads for problematic soil regions.
Keywords: thickness, CLC slab panel, flexural capacity, minimum load